Measurement of the production rate of the charm jet recoiling against the W boson using the D0 detector at the Fermilab Tevatron Collider - Ahsan, Mahsana (Kansas State University, 2008)
This dissertation describes the measurement of the rate of the associated production of the W boson with the charm jet in the proton and anti-proton collisions at the center-of-mass energy of 1.96 TeV at the Fermilab Tevatron Collider. The measurement has direct sensitivity to the strange quark content inside the proton. A direct measurement of the momentum distribution of the strange quark inside the proton is essential for a reliable calculation of new physics signal as well as the background processes at the collider experiments. The identification of events containing a W boson and a charm jet is based on the leptonic decays of the W boson together with a tagging technique for the charm jet identification based on the semileptonic decay of the charm quark into the muon. The charm jet recoiling against the W boson must have a minimum transverse momentum of 20 GeV and an absolute value of pseudo rapidity less than 2.5. This measurement utilizes the data collected by the D0 detector at the Fermilab Collider. The measured rate of the charm jet production in association with the W boson in the inclusive jet production with the W boson is 0.074 +/- 0.023, which is in agreement with the theoretical predictions at the leading order in Quantum Chromodynamics.
Keywords: Physics, Elementary Particles and High Energy (0798)